Analisa Potensi Ekonomi Daerah Dalam Rangka Penyusunan Kebijakan Pembangunan RPJMD Kabupaten Pasaman Tahun 2021-2026 - Lusi Dewiana (Education Achievement: Journal of Science and Research, 2022)
The results of the calculation of the LQ of the three basic sectors show a stable value from 2016 to 2020, where the Agriculture, Forestry and Fisheries Sector is stable above 2 (two), the Water Supply Sector, Waste Management, Waste and Recycling and the Government Administration Sector, Defense and Mandatory Social Security are stable above number 1 (one) The three basic sectors obtained are relevant to the mission of the Regional Head, namely the Agriculture, Forestry and Fisheries Sector which is relevant to mission 5 "Realizing a People's Economy Based on Local Excellence", the Water Supply, Waste Management, Waste and Recycling Sector is relevant to mission 4 "Improving Infrastructure Capacity ” and the Mandatory Government Administration, Defense and Social Security Sector relevant to mission 6 “Realizing Good and Clean Governance”. This shows that the development of the basic sector will be interrelated with the achievement of the RPJMD mission. So with a focus on developing the three basic sectors, it will support the achievement of missions 4, 5 and 6 of Pasaman Regency.